"From Birth to Death, From Beginning to End": Participant Experience and the Meaning of Research Participation in a Longitudinal Birth Cohort Study. (May 2022) - Rönkä, Anna Reetta
Research participants are vital for the success of a birth cohort study. Despite their scientific importance and large participant numbers, research on participant experience in birth cohort studies is scarce. This study explores participant experience, its different dimensions and meaning of the experience for the participants' lives. The data comes from the Northern Finland Birth Cohort 1966. In total, 49 semi-structured interviews were conducted with participants having full participation records and then subjected to qualitative content and thematic analysis. According to the findings, the participant experience is multidimensional, consisting of four dimensions; personal, relational, societal, and scientific. The experience evoked both positive and negative feelings and a sense of belongingness. Motivations to continue, perceived benefits of the study, consequences of participation, and the theme of trust were grouped under the four dimensions. The meaning of the study participation, and the level of personal investment and involvement in the study varied a lot among active study participants, forming a continuum from a very strong to a weak. The findings of this study contribute to the theoretical conceptualization of the participant experience. They help to better understand the participant's perspective, and the different aspects that participating in a longitudinal research project may entail as a subjective and a relational experience. The results may contribute to research design and aid in enhancing participant satisfaction. That is important, as conducting high-quality research depends on motivated and committed research participants.